4
$\begingroup$

I need to prove this, today my Instructor solved an integral using this formula but didn't gave a proof $$\displaystyle \int_{0}^{\infty}\dfrac{x^{s-1}}{e^{x}-1}\,dx=\zeta(s).\Gamma(s) $$ i tried to solve it using a series of $e^{x}$ but ended up nowhere.

$\endgroup$
10
$\begingroup$

We have $\int_{0}^{+\infty}z^{s-1}e^{-z}\,dz = \Gamma(s)$ for any $s>0$ by the very definition of the $\Gamma$ function.
Moreover $$ \frac{1}{e^x-1} = e^{-x}+e^{-2x}+e^{-3x}+\ldots $$ with uniform convergence over any compact subset of $\mathbb{R}^+$.
By the dominated convergence theorem it follows that $$\begin{eqnarray*} \int_{0}^{+\infty}\frac{x^{s-1}}{e^x-1}\,dx &=& \sum_{n\geq 1}\int_{0}^{+\infty}x^{s-1}e^{-nx}\,dx\\ &\stackrel{x\mapsto z/n}{=}& \sum_{n\geq 1}\frac{1}{n^s}\int_{0}^{+\infty}z^{s-1}e^{-z}\,dz\\&=&\Gamma(s)\sum_{n\geq 1}\frac{1}{n^s}\\&=&\Gamma(s)\,\zeta(s)\end{eqnarray*}$$ as wanted.

$\endgroup$
  • 2
    $\begingroup$ better: monotone convergence $\endgroup$ – Rüdiger Apr 12 '17 at 20:59
0
$\begingroup$

From Ramanujan's Master Theorem we know.... $\int_{0}^{\infty} x^{s-1} \sum_{0}^{\infty} \phi({k}){(-1)^k}\frac{x^k}{k!} dx=\Gamma({s})\phi({-s})$

If we put $\zeta(-k)$ in place of $\phi(k)$ then we get...

$\int_{0}^{\infty} x^{s-1} \sum_{0}^{\infty} \zeta({-k}){(-1)^k}\frac{x^k}{k!} dx=\Gamma({s})\zeta({s})$

or, $\int_{0}^{\infty} x^{s-1} \sum_{0}^{\infty} (\sum_{1}^\infty n^{k}){(-1)^k}\frac{x^k}{k!} dx=\Gamma({s})\zeta({s})$

$\int_{0}^{\infty} x^{s-1} \sum_{1}^{\infty} (\sum_{0}^\infty \frac{(-nx)^k}{k!}) dx=\Gamma({s})\zeta({s})$

$\int_{0}^{\infty} x^{s-1} \sum_{1}^{\infty} (e^{-x})^n dx=\Gamma({s})\zeta({s})$

$\int_{0}^{\infty} \frac{x^{s-1}}{e^{x}-1} dx=\Gamma(s)\zeta(s)$

$\endgroup$
  • $\begingroup$ Did you ever look at a proof of Ramanujan master theorem ? If you do you'll see how it is ridiculous to use it here. $\endgroup$ – reuns Aug 8 at 5:08
  • $\begingroup$ Also how do you know that $ \int_{0}^{\infty} e^{-x} \sum_{0}^{\infty} \zeta({-k}){(-1)^k}\frac{x^k}{k!}$ converges. $\endgroup$ – reuns Aug 8 at 5:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.